Sistem Informasi Stok Barang Berbasis Web Menggunakan Metode Rapid Application Development (RAD) : Studi Kasus Saung Qubil - Umah, Nadiatul; Firmansyah, Andri (Jurnal Teknologi Komputer dan Informasi, 2026)
Advancements in information technology have contributed significantly to improving the efficiency of inventory management. Saung Qubil, a culinary business, still applies a manual stock recording system that creates risks of recording errors, data loss, and delays in report preparation. This study aims to design a web-based inventory information system to support computerized inventory data management. The system development method used in this research is Rapid Application Development (RAD), which emphasizes rapid system development and active user involvement throughout the development process. The results show that the web-based inventory information system is able to improve the effectiveness, speed, and accuracy of inventory management. The system is also capable of generating inventory reports automatically, making the monitoring process more efficient. Based on interview results with users, the implementation of the system increased data recording efficiency by up to 60% compared to the previous manual system. Therefore, the implementation of a web-based inventory information system using the Rapid Application Development (RAD) method is proven to be effective in improving inventory management efficiency at Saung Qubil.